2022
DOI: 10.3390/molecules27103254
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cryoprotective and Cytoprotective Agents in Cryopreservation: A Focus on Melatonin

Abstract: Cryoprotective and cytoprotective agents (Cytoprotective Agents) are fundamental components of the cryopreservation process. This review presents the essentials of the cryopreservation process by examining its drawbacks and the role of cytoprotective agents in protecting cell physiology. Natural cryoprotective and cytoprotective agents, such as antifreeze proteins, sugars and natural deep eutectic systems, have been compared with synthetic ones, addressing their mechanisms of action and efficacy of protection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 98 publications
(149 reference statements)
1
19
0
Order By: Relevance
“…The results of the present study indicated that adding glycine at a concentration of 1.0 mM could alleviate the mechanical and osmotic injury that occurred during the vitrification process (Bojic et al, 2021;Marcantonini et al, 2022;Pegg, 2007). Here in, we found that the post-warming viability was the highest in the group supplemented with 1.0-mM glycine indicating the positive impact of this concentration on the survivability of vitrified/warmed COCs.…”
Section: Discussionsupporting
confidence: 60%
“…The results of the present study indicated that adding glycine at a concentration of 1.0 mM could alleviate the mechanical and osmotic injury that occurred during the vitrification process (Bojic et al, 2021;Marcantonini et al, 2022;Pegg, 2007). Here in, we found that the post-warming viability was the highest in the group supplemented with 1.0-mM glycine indicating the positive impact of this concentration on the survivability of vitrified/warmed COCs.…”
Section: Discussionsupporting
confidence: 60%
“…At the cellular level, its toxicity depends on different mechanisms, including membrane effects, alterations in cellular permeability, and interactions with cellular proteins and mitochondrial function. Several strategies have been proposed to minimize the toxicity of cryoprotective agents, including the combination of chemical agents with different levels of toxicity with less toxic or neutralizing cryoprotective agents (Marcantonini et al, 2022), as well as the combination of cryoprotective agents and antioxidants to reduce cell damage caused by osmotic dehydration, the formation of large ice crystals and the incidence of reactive oxygen species (ROS) during cooling and rewarming, thus improving the efficiency of cryopreservation (Liu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin, a type of indoleamine and free radical scavenger, has been reported to exhibit various antioxidative effects through G-protein-coupled receptors (GPCR). Recently reported studies have focused on the protective effect of melatonin in maintaining fertility in several species of animals and humans [ 25 , 27 , 28 , 29 , 30 , 31 , 34 , 39 , 137 , 138 , 139 ]. Even in humans, melatonin has been reported to be very useful as a sperm cryoprotectant and it has a significant effect on the toxicity and damage recovery of frozen sperm.…”
Section: Biomaterials In Gamete and Embryo Cryopreservationmentioning
confidence: 99%